2014
DOI: 10.1038/bmt.2014.131
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic hematopoietic cell transplantation for myelofibrosis using fludarabine-, intravenous busulfan- and low-dose TBI-based conditioning

Abstract: Graft failure is one of the major barriers to the success of allogeneic hematopoietic cell transplantation (HCT) in myelofibrosis (MF). We report our institutional experience with 27 MF patients who underwent HCT using fludarabine-, intravenous BU-and low-dose total body irradiation (FBT)-based reduced-intensity (n = 20) or full-intensity (n = 7) conditioning regimens. Eight patients had prior exposure to JAK1/2 inhibitor therapy; six patients received JAK1/2 inhibitors leading on to HCT and two patients recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 41 publications
2
19
2
1
Order By: Relevance
“…In general, patients with splenomegaly appear to have delayed engraftment, which nevertheless does not appear to affect the OS. 36,83 Interestingly, a French study noted a favorable survival for male patients who underwent pretransplant splenectomy, while a German study demonstrated a higher relapse rate in the splenectomized patients. 17,84 In addition, there appears to be no agreement as to the actual size of the spleen which might, or might not, serve as a trigger for pretransplant therapy.…”
Section: Impact Of Targeting the Jak/signal Transducers And Activatormentioning
confidence: 99%
See 1 more Smart Citation
“…In general, patients with splenomegaly appear to have delayed engraftment, which nevertheless does not appear to affect the OS. 36,83 Interestingly, a French study noted a favorable survival for male patients who underwent pretransplant splenectomy, while a German study demonstrated a higher relapse rate in the splenectomized patients. 17,84 In addition, there appears to be no agreement as to the actual size of the spleen which might, or might not, serve as a trigger for pretransplant therapy.…”
Section: Impact Of Targeting the Jak/signal Transducers And Activatormentioning
confidence: 99%
“…Although some studies use complete resolution of reticulin fibrosis to define a complete 'histopathologic' response to allo-SCT, in the presence of full-donor chimerism, the significance of persistent fibrosis 412 months after allo-SCT is uncertain and may not necessarily be indicative of persistent or relapsed disease. 14,36 More recently, the importance of the rate of decline of BM fibrosis has been demonstrated, with patients having a rapid regression have the best outcomes (Table 3). 15,37 In the study conducted by Kroger et al, patients who achieved a complete or near-complete resolution of fibrosis on day +100 post allo-SCT had the best OS and this was independent of the International Prognostic Scoring System (IPSS) score at the time of transplant.…”
Section: Clinical Impact Of Bone Marrow Histologymentioning
confidence: 99%
“…The reduction of proinflammatory cytokines and the suppressive effect on T cells and NK cells may have some impact on the occurrence of graft-versus-host disease (GvHD after allogeneic stem cell transplantation) [65][66][67][68]. Early data using ruxolitinib before transplantation in order to reduce spleen size and constitutional symptoms have shown feasibility and did not negatively affect outcome of transplantation [65,69,70]. Only one prospective French study reported about cardiac toxicity and tumor lysis syndrome [71].…”
Section: Role Of Splenectomy and Jak Inhibitionmentioning
confidence: 99%
“…Reduced spleen size may aid faster hematologic recovery 42 Myelosuppressive properties of JAK 1/2 inhibitors may impact hematologic recovery after HCT, limiting post-HCT use…”
Section: Reduced Splenomegaly Hematopoietic Recoverymentioning
confidence: 99%
“…36,38,[41][42][43][44][45][46] The key questions have been how to best integrate JAK inhibitor therapy into HCT protocols prior to transplant and whether there is any role in the posttransplant setting.…”
Section: Q3 Jak Inhibitors In Transplant Protocols: Beneficial or Hamentioning
confidence: 99%